Sponge Hyrtios reticulatus: Phytochemicals and Bioactivities - Mahfur, Mahfur (Research Journal of Pharmacy and Technology, 2022)
Sponge is one of the marine organisms that contribute greatly to the diversity of compounds in marine. Hyrtios reticulatus, a marine sponge of genus Hyrtios, is a structurally rich source of various metabolites. Hyrtios reticulatus can be found in various places. So far several reports have mentioned that this species has not been widely published except those originating from Indonesia especially Makassar island, Papua New Guinea, Vanuatu, and collections from the National Cancer Institute in London. Every sample taken from different places has different secondary metabolites due to the different physical and chemical conditions found in the oceans, causing the sample to have a diverse bioactivity. The secondary metabolites obtained from sponge Hyrtios reticulatus obtained from sponges from different places are shown in the articles published so far contain 19 compounds, they are obtained from sponge with different places. It is 1,6-dihydroxy-1,2,3,4-tetrahydro-β-carbolin (1), serotonin (2), 6-hydroxy-1-methyl-1,2,3, 4-tetrahydro-β-carboline (3), 6-hydroxy-3,4-dihydro-1-oxo-β-carboline (4), hyrtiocarboline (5), sacrotride A (6), 1-O-hexadecyl-sn-glycero-3-phosphocholine (7), heteronemin (8), puupehenone (9), 3-carboxy-6-hydroxy-β-carboline (10), hyrtioreticulins A–E (11-15), hyrtioerectine B (16), hyrtioreticulin F (17) reticulatins A (18), and B (19). This review emphasizes the phytochemicals of the secondary metabolites and bioactivity of the sponge Hyrtios reticulatus. This article highlights how to obtain active compounds and bioactivity from these compounds from sponge Hyrtios reticuatus. © RJPT All right reserved.